The covid-19 pandemic, force majeure and changed contractual circumstances - Varsi Rospigliosi, Enrique; Rosenvald, Nelson; Torres Maldonado, Marco Andrei (Acta Bioethica, 2020)
The declaration of a state of emergency due to the covid-19 pandemic requires an analysis of the validity of the contractual relations and how these may be affected by extraordinary, unforeseeable and irresistible events that prevent the performance of the services, as well as those cases in which the alteration of circumstances may lead one of the parties to demand that the judge recompose the content of the agreed service or terminate the contract.